PENYALAHGUNAAN KEWEWENANGAN DISKRESI PEJABAT EKSEKUTIF PEMERINTAH INDONESIA : STUDI KASUS RATU ATUT CHOSIYAH - Rifqi Arif Maulana (Universitas Islam Syekh Yusuf, 2022)
The abuse of authority within the discretionary authority by Ratu Atut Chosiyah is a concrete proof that the current system of procurement of goods and services still has weaknesses even though it has been regulated in Presidential Regulation Number 12 of 2021 (PERPRES) concerning Amendments to Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods/Services (State Gazette of the Republic of Indonesia Number 63 of 2021). This study explains the weakness of the procurement system for goods and services associated with discretionary authority in the administration of government by using the juridical-normative method so that it can provide a solution that there is an urgency to make changes to existing laws to protect tax money originating from the community to be misused by government officials. Indonesia. Keywords: discretionary authority; administration of government; procurement of goods and services.